Beyond Language: English Education in The Era of Advanced Learning - Sofiana, Isnaeni (Universitas Muhammadiyah Surakarta, 2025)
The rapid advance of developed education and learning systems has transformed the landscape of English education worldwide. Globalization, digitalization, and the increasing demand for 21st-century skills necessitate that English language teaching (ELT) move beyond traditional methods and adopt innovative pedagogical frameworks. In this context, English is not only a subject of study but also a key competency for global communication, academic achievement, and professional success. This paper examines the role of English education in advanced learning environments, highlighting critical issues such as the integration of digital platforms, the promotion of learner autonomy, the cultivation of critical thinking, and the incorporation of sustainability into language acquisition.Drawing on a mixed-methods approach that combines surveys, interviews, and classroom observations, the study investigates how students and teachers perceive the benefits and challenges of advanced learning practices in English classrooms. Findings reveal that digital tools such as Grammarly, Write & Improve, and other AI-based platforms play a significant role in enhancing language accuracy and learner motivation, yet they also risk fostering overdependence and reducing deeper engagement with language use. The paper argues that English education must strategically integrate technology, global competencies, and critical pedagogy to align with the goals of advanced learning. It concludes by offering recommendations for curriculum innovation, teacher professional development, and institutional support to foster sustainable and future-ready English education.